Comparison of the Method of Least Squares and the Simplex Method for Processing Geodetic Survey Results - Gašincová, Silvia; Gašinec, Juraj (GeoScience Engineering, 2013)
The present paper is devoted to the use of the simplex method in the processing of results from geodetic measurements as compared with the standard used method of least squares. Using the simplex method, a minimization problem is usually solved in a standard tabular form by rearranging lines and columns in order to find an optimal solution. The paper points out the simpler, more stable and more efficient way to solve a problem of linear programming through a matrix of relations.